2016
DOI: 10.1016/j.jjcc.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of coronary calcium in asymptomatic Japanese subjects in lung cancer screening computed tomography

Abstract: The results of this study provide a pattern of CAC distribution based on age and gender in asymptomatic Japanese subjects. This pattern was similar to that in Western countries, although the absolute CAC scores were lower. High CAC scores were associated with male gender, aging, dyslipidemia, and fasting glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
3
17
3
Order By: Relevance
“…Among these, 12 studies fulfilled the inclusion criteria and contained all information necessary to create the new CAC score nomogram and were therefore included in this analysis. 10,[14][15][16][17][18][19][20][21][22][23][24] The reasons for exclusion of potentially eligible studies are provided in Supplemental Fig. 1.…”
Section: Search and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, 12 studies fulfilled the inclusion criteria and contained all information necessary to create the new CAC score nomogram and were therefore included in this analysis. 10,[14][15][16][17][18][19][20][21][22][23][24] The reasons for exclusion of potentially eligible studies are provided in Supplemental Fig. 1.…”
Section: Search and Selectionmentioning
confidence: 99%
“…A total of 134,336 asymptomatic patients from the western hemisphere were included, 10,14-22 of which 34% were women and 19% were under the age of 45 years. In the analyses of Asians, a total of 33,488 asymptomatic individuals were included, 13,14,23,24 of which 18% were women and 12% were under the age of 45 years.…”
Section: Characteristics Of the Studies Included In The Analysesmentioning
confidence: 99%
“…Notably, none of these publications evaluate the correlation of coronary calcium with cardiovascular morbidity and mortality. The prevalence and distribution of coronary calcium have been described in Japan (21). In a cohort of 1,834 lung cancer screening studies, a non-zero calcium score was detected in 26.9% of all subjects.…”
Section: Asiamentioning
confidence: 99%
“…In 2015, epidemiological data indicated that mortality and incidence rates of pulmonary carcinoma continue to increase . A study employing a Japanese cohort estimated that 26.5% of patients diagnosed with pulmonary carcinoma also had different degrees of coronary heart disease (CHD) . The perioperative risk of cardiovascular events in such patients is estimated to be as high as 4.2% …”
Section: Introductionmentioning
confidence: 99%
“…1 A study employing a Japanese cohort estimated that 26.5% of patients diagnosed with pulmonary carcinoma also had different degrees of coronary heart disease (CHD). 2 The perioperative risk of cardiovascular events in such patients is estimated to be as high as 4.2%. 3,4 In patients with pulmonary carcinoma combined with CHD, percutaneous coronary intervention (PCI) is considered the most effective method to reduce the occurrence of postoperative acute coronary syndrome (ACS).…”
Section: Introductionmentioning
confidence: 99%